Train-Induced Fluctuating Pressure and Resultant Dynamic Response of Semienclosed Sound Barriers - Jing Zheng; Qingliang Li; Xiaozhen Li; Yunke Luo (Shock and Vibration)
This paper reports on train-induced fluctuating pressure and consequent dynamic response of semienclosed sound barriers (SESBs), a novel type of sound barriers. A computational fluid dynamic (CFD) model and a finite element (FE) model were established. The in situ vibration measurement of the SESB was introduced for the first time. Pressure-induced vibrations were extracted from the measured results. The analyzing process of the pressure-induced vibration below 20 Hz is verified. Influencing factors of the pressure and vibrations, including train running on the near- or far-line and the length effect of total top plates, were finally discussed with the dimensionless method. Results show that the distribution of pressure is significantly different, but the vibration laws are similar whether the train is running on the near- or far-line. The longer is the total length of the top plates, the larger are the pressure and vibration on the inner surface.